Effects of Interaction Between Dopamine D2 Receptor and Monoamine Oxidase A Genes on Smoking Status in Young Men. (July 2015) - Huang, Chih-Ling; Ou, Wei-Chih; Chen, Pei-Lain; Liu, Chen-Nu; Chen, Mei-Chih; Lu, Chia-Chen; Chen, Yi-Chun; Lin, Min-Hsuan; Huang, Ching-Shan
Although the effect of gene–gene interaction on nicotine–dopamine metabolism for smoking behavior has been reported, polymorphisms of dopamine D2 receptor ( DRD2 ) and monoamine oxidase A ( MAOA ) have not been simultaneously examined among smokers. In this study, 481 young Taiwanese men completed a self-report questionnaire on smoking status, and data were obtained on polymorphisms of DRD2 rs1800497, DRD2 rs1079597, MAOA rs309850, and MAOA rs1137070, urinary nicotine, and urinary cotinine. In a comparison of 261 current smokers and 220 never smokers, odds ratios ( OR s) for the development of smoking in all genotypes were not statistically significant. Among smokers with DRD2 rs1079597 GG// MAOA rs309850 3-repeat, the OR of heavier smoking was 2.67 times higher (95% confidence interval [CI]: [1.08, 6.59], p = .031) and the score on the Fagerstrom test for nicotine dependence was higher (4.26 vs. 2.83) than in those with DRD2 rs1079597 AA// MAOA rs309850 3-repeat. Adjusted urinary cotinine concentration was significantly different between those two groups (median value: 95.83 ng/μl vs. 133.24 ng/μl, respectively, p = .045). These findings suggest that the interaction of DRD2 rs1079597 and MAOA rs309850 3-repeat affects smoking intensity in young Taiwanese men.